God in Nederland: inzichten en vergezichten - Ton Bernts; Gerard Dekker; Joep de Hart (Religie & Samenleving)
In the article the authors of the publication God in the Netherlands answer the critical arguments and suggestions of two reviewers. With respect to the representative character of the data, they agree that the obtained response of 45% is not very high indeed, in spite of great efforts made: respondents were contacted up to 5 times. Yet, cross validation with other recent surveys did not show significant different outcomes. As to the shortcomings of repeated crosssectional data, the authors state that a lot of attention has been paid to current religious developments, while at the same time the advantages of a trend study have been preserved. The suggestion made to include real-life practices is interesting. In answer to some topics brought forward by the reviewers, the authors underline the process of polarization, which means that the religious part of the Dutch population is getting smaller, but more religious active. Likewise they agree that the data reveal an ongoing process of compartmentalization. Furthermore, they argue that both a structural and a moral mechanism inspire active church members to be volunteers. As to contemporary spirituality, it is argued that this spirituality is indeed individualized and fragmented, but that this doesn’t mean that ‘the new spirituals’ show less social engagement. With respect to the next edition of God in the Netherlands, the authors propose to focus more on nonreligious groups and the cultural dimensions of Christianity.